PEMANFAATAN ECENG GONDOK MENJADI PUPUK DI PURI TAMAN SARI KEC. TAMALATE KOTA MAKASSAR - A.Rachmat Wirawan; Nuraziza Aliah (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Water hyacinth (Eichornia crassipes) is an aquatic plant belonging to a weed that thrives in lakes and rivers throughout Indonesia. The water hyacinth plant was later categorized as a pest because it was considered a threat to the ecosystem by reducing the number of native species and causing negative impacts on socio-economic aspects such as silting of waters, destruction of fishery habitats and being one of the factors for flooding with overflowing river water. In addition, the process of cleaning water hyacinth by the local government janitor results in the buildup of water hyacinth on the shoulder of the road, making the environment look dirty and slum as well as narrowing access to vehicle paths which results in congestion. Water hyacinth (Eichornia crassipes) is a plant that becomes aquatic waste and its presence has not been widely used (Megawati 2015: 42). The purpose of this PKM is how to overcome water hyacinth problems and utilize water hyacinth as fertilizer. The method used in this PKM activity is by making direct observations to the partner's place in Puri Taman Sari, Kec. Tamalate Makassar City, which was then continued by conducting training to local community groups regarding the processing of water hyacinth into fertilizer using the composting method. The activity was carried out by dividing the residents into several small groups and each group being given technical training in making tools and how to process water hyacinth into fertilizer. By processing water hyacinth by residents, it produces 2 (two) types of fertilizers, namely in solid form (compost) and in liquid form which have been tested on residents' plants. From this activity, solutions have been found on how to overcome the problem of environmental pollution by water hyacinth and become effective and useful goods for the community. Tanaman Enceng Gondok (Eichornia crassipes) merupakan tanaman air yang tergolong gulma yang banyak tumbuh subur di danau maupun di sungai di seluruh Indonesia. Tanaman enceng gondok belakangan dikategorikan sebagai hama karena dianggap mengancam ekosistem dengan menurunkan jumlah spesies asli dan menimbulkan dampak negatif pada aspek sosial ekonomi seperti pendangkalan perairan, rusaknya habitat perikanan serta menjadi salah satu faktor terjadinya banjir dengan peluapan air sungai. Selain itu proses pembersihan enceng gondok oleh petugas kebersihan pemerintah setempat mengakibatkan penumpukan enceng gondok di bahu jalan menjadikan lingkungan terlihat kotor dan kumuh juga mempersempit akses jalur kendaraan yang berimbas pada kemacetan. Enceng Gondok (Eichornia crassipes) merupakan tanaman yang menjadi limbah perairan dan keberadaannya belum banyak dimanfaatkan (megawati 2015 : 42) . Tujuan dari PKM ini adalah bagaimana mengatasi permasalahan enceng gondok serta memanfaatkan enceng gondok menjadi Pupuk. Metode yang digunakan pada kegiatan PKM ini yakni dengan melakukan observasi langsung ke tempat mitra di Puri Taman Sari Kec. Tamalate Kota Makassar yang kemudian dilanjutkan dengan melakukan pelatihan kepada kelompok warga setempat terkait pengolaan enceng gondok menjadi pupuk dengan metode komposting. Kegiatan dilakukan dengan membagi warga kedalam beberapa kelompok kecil dan setiap kelompok diberikan pelatihan teknis pembuatan alat dan cara mengolah enceng gondok menjadi pupuk. Dengan pengolaan enceng gondok oleh warga menghasilkan 2 (dua) macam jenis pupuk yakni dalam bentuk padat (kompos) dan dalam bentuk cair yang telah diujicobakan terhadap tanaman warga. Dari kegiatan ini telah ditemukan solusi bagaimana mengatasi masalah pencemaran lingkungan oleh enceng gondok serta menjadi barang berhasil guna dan bermanfaat bagi masyarakat.